Tech Revolution in HR: Leveraging AI for Smarter Talent Acquisition - Herman Sjahruddin; Jeziano Rizkita Boyas; Deri Prayudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the intricate interplay between talent acquisition effectiveness , quality of recruitment , the HR adjustment department , and the adoption of artificial intelligence in HR practices within PT. Pharos Indonesia. Using quantitative analysis techniques, data was gathered from a sample of employees to explore the direct and sequential relationships between these variables. The results reveal significant pathways, indicating that higher levels of artificial intelligence are associated with more effective HR adjustment departments, which may in turn lead to a greater propensity to adopt AI technologies in HR processes. While the direct relationship between quality of recruitment and AI did not reach statistical significance, the sequential relationship via HR adjustment departments showed marginal significance, underscoring the importance of recruitment quality in indirectly influencing AI adoption. These findings highlight the strategic significance of optimizing talent acquisition strategies and HR adjustment practices as precursors to leveraging AI's transformative potential in HR management, ultimately contributing to organizational resilience and competitiveness. Further research is recommended to delve deeper into the underlying mechanisms and implications for HR practices and organizational performance.